Integrating PLM and Digital Twin Technologies: A Comprehensive Analysis of Modern Product Development - Jasleen Singh Saini (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the integration of Product Lifecycle Management (PLM) systems with Digital Twin technology and its transformative impact on modern product development processes. The article examines how this integration enhances operational efficiency, enables real-time monitoring, and facilitates predictive maintenance across various industrial sectors. It explores the technical framework required for successful implementation, including data management systems, collaborative environments, and simulation capabilities. The article also addresses industry-specific applications in manufacturing, aerospace, and healthcare sectors, highlighting how different industries leverage these technologies for improved productivity and innovation. The article discusses critical technical challenges in data interoperability and system integration, along with their solutions, and explores future developments in AI/ML integration and emerging technologies, providing insights into the evolving landscape of digital transformation in product development.